The influence of organisational culture on work discipline with organisational justice as an intervening variable (Case study at the Population and Civil Registration Office of Kerinci District) - Suhelmi Helia; Elly Hendrayati; Apral Darman; Diat Tri Hananda; Yasmirwati Yasmirwati (Institute of Computer Science (IOCS), 2023)
This study reveals key findings related to the influence of Organizational Culture and Organizational Justice on Work Discipline at the Population and Civil Registration Office of Kerinci Regency. The results of path analysis show that Organizational Culture has a significant direct influence on Organizational Justice (54.7%) and Work Discipline (53.4%). Organizational Justice also affects Work Discipline directly with a contribution of 15%. In addition, there is a significant indirect effect of Organizational Culture on Work Discipline through Organizational Justice, with a contribution of 61.6%. These results highlight the importance of Organizational Justice as a mediator in understanding how Organizational Culture shapes employee Work Discipline. The main conclusion is that efforts to improve Work Discipline can be enhanced through improving Organizational Culture and Organizational Justice. A better understanding of these relationships can assist management in developing more effective strategies to create a disciplined and equitable work environment. The practical implications of this study can assist organizations in designing more targeted policies and training programs to improve employee performance and positive attitudes.